The Priority Need in Innovative Leadership of Krittasilphwittaya School’s Teachers - Khotta, Weerasak; Jariyarangsiroge, Apiradee (Interdisciplinary Academic and Research Journal, 2023)
Education is one of the forces that drives and develops the potential of future personnel who are ready for changes based on technology. Hence the new face of the education system must be an education system called "Intelligent Education System or Education 5.0". Innovative Leadership is therefore an important competency that school administrators and teachers must have. Teachers play a very important role in teaching and learning development. Teachers must therefore be individuals who are ready to learn innovations. to develop responsible work to achieve goals. This study, then, aims to examine the current situation, desirable conditions, and the need for innovative leadership development of teachers at Krittasilphwittaya School. This study used descriptive research methodology. The population consists of 66 administrators and teachers of Krittasilphwittaya School. The research tools were a questionnaire about the present condition and the desirable condition of the teachers at Kritsilphwittaya School. Data were analyzed using the Statistical Package for Social Science then analyzed the needs and necessities of the present and desirable conditions of innovative leadership of Krittasilphwittaya School teachers. The obtained data was analyzed to find the index of necessary needs from the Modified Priority Needs formula and ranked the needs as necessary. The findings revealed that (1) the innovative leadership status of Krittasilphwittaya School teachers was at a low level, Learning ability, and thinking skills were at a low level, Management, and innovation management abilities were at a moderate level and Teamwork were at a low level and the overall need index for innovative leadership development of Krittasilphwittaya School teachers was at a high level, with The requirement to develop teamwork learning ability and thinking skills and management and innovation management abilities, respectively. (2) Recommendations from the research include: Administrators of Krittasilphwittaya School should develop a project to develop teachers’ potential in terms of continuous learning, should organize a competition among teachers in creating innovative management guidelines to practice management skills and manage innovation And there are prizes from the competition as an incentive to do activities, and should promote teamwork by organizing sports competitions between teachers and staff or organizing field trips for teachers and staff to promote good relationships between teams.